What Do Proofreaders of Student Writing Do to a Master's Essay? Differing Interventions, Worrying Findings. (October 2018) - Harwood, Nigel
There has been much interest recently in researching the changes editors, supervisors, and other language brokers make to the writing of L2 researchers who are attempting to publish in English. However, studies focused on the presubmission proofreading of students' university essays are rarer. In this study of student proofreading, 14 UK university proofreaders all proofread the same authentic, low-quality master's essay written by an L2 speaker of English to enable a comparison of interventions. Proofreaders explained their interventions by means of a talk aloud while proofreading and at a post-proofreading interview. Quantitative and qualitative analysis of the data reveals evidence of widely differing practices and beliefs, with the number of interventions ranging from 113 to 472. Some proofreaders intervened at the level of content, making lengthy suggestions to improve the writer's essay structure and argumentation, while others were reluctant to do more than focus on the language. Disturbingly, some proofreaders introduced errors into the text while leaving the writer's errors uncorrected. I conclude that the results are cause for deep concern for universities striving to formulate ethical proofreading policies.